2019
DOI: 10.1128/msystems.00638-19
|View full text |Cite
|
Sign up to set email alerts
|

Marine Metabolomics: a Method for Nontargeted Measurement of Metabolites in Seawater by Gas Chromatography–Mass Spectrometry

Abstract: Nontargeted approaches using metabolomics to analyze metabolites that occur in the oceans is less developed than those for terrestrial and limnic ecosystems. One of the challenges in marine metabolomics is that salt limits metabolite analysis in seawater to methods requiring salt removal. Building on previous sample preparation methods for metabolomics, we developed SeaMet, which overcomes the limitations of salt on metabolite detection. Considering that the oceans contain the largest dissolved organic matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…For example, phytoplankton release alcoholcontaining polysaccharides, 13 that may compete with metabolites for BC or preferentially adhere to the PPL, thereby lowering analyte retention. The seawater DLs obtained in this study are generally similar in magnitude to those reported by Johnson et al 16 and lower than those reported by Sogin et al 15 The DLs reported here were sufficiently sensitive to detect numerous metabolites in culture media and at BATS (Table S8). CONCLUSIONS Our pre-extraction benzoylation method substantially improves the detection and quantification of small, highly polar, dissolved metabolites in seawater and saline culture medium.…”
Section: Resultssupporting
confidence: 84%
“…For example, phytoplankton release alcoholcontaining polysaccharides, 13 that may compete with metabolites for BC or preferentially adhere to the PPL, thereby lowering analyte retention. The seawater DLs obtained in this study are generally similar in magnitude to those reported by Johnson et al 16 and lower than those reported by Sogin et al 15 The DLs reported here were sufficiently sensitive to detect numerous metabolites in culture media and at BATS (Table S8). CONCLUSIONS Our pre-extraction benzoylation method substantially improves the detection and quantification of small, highly polar, dissolved metabolites in seawater and saline culture medium.…”
Section: Resultssupporting
confidence: 84%
“…Thus, either secreted by live cells or released upon cell lysis, sucrose is expected to be available as a carbon source in marine ecosystems. In support of this idea, a recent metabolomics study has reported the detection of abundant sugars, which included sucrose and trehalose, in marine ecosystems [85], and sucrose has also been detected as a major nutrient available in seagrass (Posidonia oceanica) meadows ecosystems [86]. It is also expected that the digestive tracts of marine herbivores as sea urchins and algae grazers among others, constitute a sucrose-rich niche for bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, reasonable signals are achievable with a few hundred mL to a few L of seawater for both dissolved and particulate metabolites. Smaller volumes can be used for metabolite analysis by gas chromatography (GC) MS (Sogin et al, 2019) but fewer molecules are accessible to the derivatization required for GC analysis.…”
Section: Analysis Of Polar Biologically Labile Organic Moleculesmentioning
confidence: 99%